Personnel Management in Canada - Matejko, Alexander J. (Relations Industrielles / Industrial Relations, 1984)
This article reviews the book, "Personnel Management in Canada," by Thomas H. Stone & Noah M. Meltz.

Worker Capitalism. The New Industrial Relations - Matejko, Alexander J. (Relations Industrielles / Industrial Relations, 1984)
This article reviews the book, "Worker Capitalism. The New Industrial Relations," by Keith Bradley & Alan Gelb.

Trade Unions : The logic of Collective Action ; The Economics of Trade Unions - Matejko, Alexander J. (Relations Industrielles / Industrial Relations, 1984)
This article reviews the book, "Trade Unions : The logic of Collective Action," by Colin Crouch. This article reviews the book, "The Economics of Trade Unions," by Albert Rees.

Workplace Industrial Relations in Britain - Matejko, Alexander J. (Relations Industrielles / Industrial Relations, 1984)
This article reviews the book, "Workplace Industrial Relations in Britain," by W.W Daniel & Neil Millward.

The Humanisation of Work - Matejko, Alexander J. (Relations Industrielles / Industrial Relations, 1984)
This article reviews the book, "The Humanisation of Work," by Dan Ondrack & Timperley Stuart.

Under Japanese Management. The Experience of British Workers - Matejko, Alexander J. (Relations Industrielles / Industrial Relations, 1984)
This article reviews the book, " Under Japanese Management. The Experience of British Workers," by Michael White & Malcolm Trevor.

Upward Mobility - Matejko, Alexander J. (Relations Industrielles / Industrial Relations, 1984)
This article reviews the book, "Upward Mobility," by The Staff of Catalyst.

Workers and the New Depression - Matejko, Alexander J. (Relations Industrielles / Industrial Relations, 1984)
This article reviews the book, "Workers and the New Depression," by Robert Taylor.

The Nature of Work. An Introduction to Dabates on the labour Process - Matejko, Alexander J. (Relations Industrielles / Industrial Relations, 1984)
This article reviews the book, " The Nature of Work. An Introduction to Dabates on the labour Process," by Paul Thompson.

Employment Injuries and Occupational Illness 1972-1981 - Matejko, Alexander J. (Relations Industrielles / Industrial Relations, 1984)
This article reviews the book, "Employment Injuries and Occupational Illness 1972-1981," by Jim Wong.

The Japanese Industrial System - Matejko, Alexander J. (Relations Industrielles / Industrial Relations, 1984)
This article reviews the book, "The Japanese Industrial System," by Charles J. McMillan.

The Working Conditions in Canadian Hospitals. Constraints and Opportunity - Matejko, Alexander J. (Relations Industrielles / Industrial Relations, 1984)
This article reviews the book, "The Working Conditions in Canadian Hospitals. Constraints and Opportunity," by Joan Kahn & William A. Westley.

Gain and Equity Sharing. Quality of Working Life - Matejko, Alexander J. (Relations Industrielles / Industrial Relations, 1984)
This article reviews the book, "Gain and Equity Sharing. Quality of Working Life," by Donald V. Nightingale.